2018
DOI: 10.1021/acs.jafc.8b03568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Natural Flavonoid Isoorientin on Growth Performance and Gut Microbiota of Mice

Abstract: Isoorientin (ISO) is a natural flavonoid, which is a 6- C-glucoside of luteolin, and has been demonstrated to possess multiple biological properties. In this study, the effects of ISO on the growth performance and gut microbiota of BALB/c mice were investigated. The results showed that ISO could promote food intake and body weight gain, increase the digestibility of crude proteins and utilization of the gross energy, and strengthen antioxidant capacity of mice. We also demonstrated it has no side effects on he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 34 publications
1
31
0
1
Order By: Relevance
“…Significant attenuation of DSS‐induced increase in Oscillibacter were observed in all TE‐treated groups. The positive and negative effects of Oscillibacter were reported in various literature . Arpaia et al.…”
Section: Resultsmentioning
confidence: 99%
“…Significant attenuation of DSS‐induced increase in Oscillibacter were observed in all TE‐treated groups. The positive and negative effects of Oscillibacter were reported in various literature . Arpaia et al.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the abundance of certain bacteria was significantly reduced in the AMC group compared to that of the HFD group. These bacteria, including Bacteroides (Pedersen et al, 2016;Schulfer et al, 2018), Odoribacter (Schulfer et al, 2018), Parabacteroides (Kang et al, 2018), Prevotella 9 (Pedersen et al, 2016), Alistipes (Kang et al, 2018;Yuan et al, 2018), Parasutterella (Chen et al, 2018), Klebsiella (Atarashi et al, 2017), and Haemophilus (Fernández-Calvet et al, 2018) were shown to positively correlate with the inflammatory state of the body, driving insulin resistance. Further, co-metabolite analyses identified significant AMC-induced metabolite changes in the feces that could serve as potential biomarkers in improving or inducing insulin resistance, including HPLA, palmitoleic acid, dodecanoic acid, linoleic acid, and erucic acid.…”
Section: Discussionmentioning
confidence: 99%
“…GM is a key determinant of nutritional intake, energy regulation and weight control. In addition to metabolic disorders, diet also plays a fundamental role in the formation of microflora (61) . Inappropriate utilisation of antibiotics can lead to the imbalance of GM.…”
Section: Discussionmentioning
confidence: 99%